Speak more fluently and stutter more fluently approaches - their principles, strengths and limitations - Berquez, Ali (Henry Stewart Talks, 2016)
Three approaches to direct speech management in stuttering: speak more fluently, stutter more fluently and integrated approaches, Overview of each approach, their strengths and limitations, Video demonstration of four techniques: soft articulatory contacts; continuous voicing; freezing and voluntary stuttering, Clinical decision making, Transfer of skills, Maintenance